Pengaruh perbedaan jenis wadah fermentasi terhadap keberhasilan fermentasi dan kualitas biji kakao: review - Nengsi, Sulistia; Wahyudi, Vritta Amroini; Warkoyo, Warkoyo (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
This paper aims to determine the effect of different types of fermentation containers. Fermentation of cocoa beans can be done using several types of fermentation containers such as fermentation boxes, bamboo baskets and styrofoam. Each type of container will produce different types of fermentation containers will influence changes in temperature and pH profiles during the cocoa bean fermentation process. In this discussion we will discuss the influence of different types of fermentation containers used on the quality of the cocoa beans produced, so that this study can provide information regarding the influence of the type of fermentation container used on the success and quality of the cocoa beans. The method used is to review several previous articles using Google School and draw conclusionsUsing wooden boxes as fermentation media will produce more optimal temperature and pH than other container types because they have insulating properties. The duration of the length of the cocoa bean fermentation process will affect the result of the moisture content of the fermented cocoa beans. The longer the cocoa fermentation process, the lower the dried cocoa beans' moisture content. Limit The maximum moisture content of cocoa beans, according to SNI, is 7.5%. The total phenolic value of fermented cocoa beans is influenced by several differences, namely differences in fruit varieties, fruit maturity levels, fermentation processes, drying, and roasting or roasting.